Erving Goffman's Dramaturgy About The Self-Existence Of Youth in "Citayam Fashion Week" - Novida IRAWAN; Sunarto SUNARTO; Ridzki Rinanto SIGIT (International Journal of Environmental, Sustainability, and Social Science, 2023)
Citayam Fashion Week is a series of events that present various images of social reality that influence people's way of thinking and behaving. This event is important because it gives youth the opportunity to meet and interact with one another. What attracts people's attention is the unique style of clothing worn by teenagers. Teenagers are looking for an identity, and they can find it by watching and participating in the Citayam Fashion Week event. This study aims to analyze dramaturgy, self-existence in impression management of Citayam Fashion Week adolescents. The paradigm in this study is constructivist, and this study uses a qualitative approach to the "Citayam Fashion Week" phenomenon as a subculture in young people's existence in the SCBD (Sudirman, Citayam, Bojong Gede And Depok). Data collection in this study used observation and in-depth interview techniques to obtain accurate results. The sampling technique used in this study was a combination of nonprobability sampling methods, between purposive sampling and snowball sampling. The research results obtained by the researchers showed that the researchers found differences in the lives of youth when they were on the front stage and when they were backstage. The conclusion is that basically, everyone will do Impression Management according to what they want to show on the frontstage, whether it is very different from life on backstage or there is only a slight difference from what it was on backstage. Teenagers have three different sides where there is a frontstage, a backstage and also transit stage.